Use of Application-Based Animation Media Regarding Dental and Oral Health Care to Increase Knowledge (Study of 12 Year Old Students at SDN 1 Kalikuning, Tulakan District, Pacitan Regency, 2024) : Penggunaan Media Animasi Berbasis Aplikasi Tentang Pemeliharaan Kesehatan Gigi Dan Mulut Dalam Meningkatkan Pengetahuan (Studi Pada Siswa Usia 12 Tahun Di SDN 1 Kalikuning Kecamatan Tulakan Kabupaten Pacitan Tahun 2024) - Prima Natawati; Ratih Larasati; IGA Kusuma Astuti (Poltekkes Kemenkes Surabaya, 2024)
Dental caries is a dental tissue disease characterized by tissue damage, starting from the surface of the tooth to the layers of enamel, dentin and pulp. The problem in this research is the high rate of DMF-T in students aged 12 years. The aim of this research is to determine the use of application-based animation media about maintaining dental and oral health in increasing knowledge among 12 year old students at SDN Kalikuning 1, Tulakan District, Pacitan Regency. The type of research used was a Quasy Experiment with a one group pretest-posttest design. The research respondents were 12 year old students at SDN Kalikuning 1 Tulakan, Pacitan Regency, totaling 49 students. The research method for collecting data in this study used a pretest-posttest questionnaire sheet to increase students' knowledge about maintaining oral health. Data analysis used the Wilcoxon Test using the SPSS data processing application. The result (improvement of prime) of this research is that the value of Asymp Sig. (2-tailed) of 0.000 < 0.05, there was an increase in knowledge of dental and oral health maintenance before and after counseling using application-based animation media. The conclusion of this research is that there is an increase in knowledge of dental and oral health maintenance, meaning that application-based animation media can increase students' knowledge about it effectively.